Association of lifestyle factors with menstrual problems and its treatment-seeking behavior among adolescent girls - Shekhar Chauhan (Elsevier, 2021)
Background: Lifestyle factors such as obesity, exercise, smoking, alcohol drinking, physical activity, and stress are related to menstrual problems among adolescents. Therefore, this study examines the association of lifestyle factors with menstrual problems among adolescent girls. Furthermore, the study also seeks to examine treatment-seeking behaviour for menstrual problems among adolescent girls. Methods: Secondary data analysis was performed on cross-sectional survey data obtained from the Understanding the Lives of Adolescents and Young Adults (UDAYA) project survey. The sample size for this study was 12,707 adolescents girls aged 10–19 years. There are two outcome variables, i.e., menstrual problem and its treatment-seeking behaviour. The study employed the heckprobit selection model, which is a two-equation model. Results: About 11% of adolescent girls suffered from menstrual problems, and among them, nearly one-third of adolescent girls sought treatment. The study noticed that menstrual problems were higher among adolescents who had severe depressive symptoms [β: 0.53; CI: 0.36, 0.70], were using substance [β: 0.03; CI: −0.24, 0.29], and were not involved in physical activity [β: 0.06; CI: −0.03, 0.15]. Adolescent girls from the richest wealth quintile were less likely to report menstrual problems [β: −0.15; CI: −0.32,-0.04], however, were 0.45 times significantly more likely to seek treatment for menstrual problems [β: 0.45; CI: 0.12, 0.78] than poorest adolescent girls. Conclusions: There is a need to focus on improving health education on puberty and menstruation that may further improve the treatment-seeking for menstrual problems among adolescent girls, specifically in rural areas.